2022
DOI: 10.3389/fmicb.2022.834091
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Suppresses Cytokines Release in cc4821 Neisseria meningitidis Infection via TLR4 and ERβ-p38-MAPK Pathway

Abstract: Estrogen has long been known to possess immune-modulatory effects in diseases, and multiple pathological conditions show great sex disparities. However, the impact of estrogen in Neisseria meningitidis infection has not been determined. The present study aimed to investigate the role of estrogen in N. meningitidis infection and the molecular mechanism. We selected 35 N. meningitidis isolates representing different clonal complexes (cc), serogroups, and isolation sources to infect the HBMEC cell line. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Protein homoeostasis is critically important for basic cellular signalling and different pathogens target these molecules to highjack host cellular machinery (Guo et al., 2022 ; Horianopoulos et al., 2021 ). AKT degradation can induce p85‐PI3 kinase (PI3K) and inhibit PI3K signalling pathway (Xu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein homoeostasis is critically important for basic cellular signalling and different pathogens target these molecules to highjack host cellular machinery (Guo et al., 2022 ; Horianopoulos et al., 2021 ). AKT degradation can induce p85‐PI3 kinase (PI3K) and inhibit PI3K signalling pathway (Xu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, Guo et al. showed that 17 β-estradiol (E2) suppressed the release of inflammatory factors via inhibiting TLR4 ( 70 ). Therefore, there is a negative relationship between estrogen and TLR4 expression.…”
Section: Clinical Significances Of Tlr4 In Osteoporosismentioning
confidence: 87%